2020
DOI: 10.1038/s41598-020-61253-2
|View full text |Cite|
|
Sign up to set email alerts
|

Plasma neutrophil extracellular trap level is modified by disease severity and inhaled corticosteroids in chronic inflammatory lung diseases

Abstract: www.nature.com/scientificreports www.nature.com/scientificreports/ a background. Measurements were conducted by BD FACSCalibur (BD Biosciences). Optimization of cytometer settings and gating strategy was carried out as described earlier for extracellular vesicle quantification [30][31][32] . For the quantification only the number of MPO/Sytox Red/histone triple positive events were considered.Human samples. Whole blood samples were collected to sodium citrate tubes from all individuals. During the blood collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Of note, the increase of NETosis in a fraction of ecu-treated patients with high neutrophil counts, despite the concomitant use of corticosteroids, likely argues against a steroid-driven effect on neutrophilia. This notion is consistent with evidence that corticosteroids can dampen neutrophil responses and NET release in lung patients [ 38 ].…”
Section: Discussionsupporting
confidence: 92%
“…Of note, the increase of NETosis in a fraction of ecu-treated patients with high neutrophil counts, despite the concomitant use of corticosteroids, likely argues against a steroid-driven effect on neutrophilia. This notion is consistent with evidence that corticosteroids can dampen neutrophil responses and NET release in lung patients [ 38 ].…”
Section: Discussionsupporting
confidence: 92%
“…Corticosteroids are a currently recommended treatment for severe COVID-19 ( 104 ) shown to reduce neutrophils’ respiratory burst and recruitment to the inflamed tissue at system level ( 105 ) and inhaled glucocorticoids have been shown to reduce NET formation in asthma patients ( 106 ). Additionally, they might have a pro-inflammatory and anti-apoptotic effect on neutrophils by reducing the levels of both, the secreted IL-1 receptor antagonist (IL-1RA) and the membrane-exposed Fas ( 105 ).…”
Section: Treatment Of Neutrophil-associated Damage In Covid-19mentioning
confidence: 99%
“…NETs play an important role in host defence, and these structures are also associated with tissue damage 5 . Several recent studies have revealed that NETs, which are associated with disease severity, are increased in a subset of patients with severe asthma 6,7 …”
Section: Introductionmentioning
confidence: 99%